2015
DOI: 10.1158/1078-0432.ccr-14-2464
|View full text |Cite
|
Sign up to set email alerts
|

Glycodelin: A New Biomarker with Immunomodulatory Functions in Non–Small Cell Lung Cancer

Abstract: Purpose: In recent years, immune therapeutic strategies against non–small cell lung cancer (NSCLC) based on tissue-derived biomarkers, for example PD1/PD-L1 (CD274), have evolved as novel and promising treatment options. However, the crosstalk between tumor and immune cells is poorly understood. Glycodelin (gene name PAEP), initially described in the context of pregnancy and trophoblastic implantation, is a secreted immunosuppressive glycoprotein with an as-of-yet largely unknown function in lung cancer. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(90 citation statements)
references
References 41 publications
7
77
1
Order By: Relevance
“…Total RNA was transcribed to sscDNA with a Transcriptor First Strand cDNA Synthesis kit (Roche Diagnostics GmbH, Mannheim, Germany). More detailed information is described elsewhere (27). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was transcribed to sscDNA with a Transcriptor First Strand cDNA Synthesis kit (Roche Diagnostics GmbH, Mannheim, Germany). More detailed information is described elsewhere (27). …”
Section: Methodsmentioning
confidence: 99%
“…CT values were calculated with the LightCycler ® 480 software version 1.5 using the 2nd derivative maximum method (Roche Diagnostics). Detailed information is described elsewhere (27). …”
Section: Methodsmentioning
confidence: 99%
“…While the polyclonal antibody stained nearly all tumor cells, the immunosuppressive form glycodelin A was only partly and inhomogeneously expressed within the tumor nests (see enlarged areas). Antibody specificity was tested and validated in controls (Figure S2) and elsewhere [29]. …”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, we showed that glycodelin was expressed in NSCLC tumors and can be used as a biomarker for monitoring of the tumor burden during the therapy [28]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation